Dual phase role of composite adsorbents made from cockleshell and natural zeolite in treating river water - Siti Nur Fatihah, Moideen; Mohd Fadhil, Md Din; Shahabaldin, Rezania; Mohanadoss, Ponraj c; Azlan, Abd Rahman; Low*, Wen Pei; Zulhilmi, Ismail; Shazwin, Mat Taib; Li, Yu-You (King Saud University, 2020)
In this study, the potential of dual-phase composite adsorbent to determine the removal efficiency of organic compounds such as COD, BOD, TP, and TN was investigated. The combination ratio of cockleshell and natural zeolite was optimized using D-optimal mixture design (DMD). The generated ratio was tested using run test in Easy Care PipeSystem (ECPS). Breakthrough curve was plotted to determine the total removal by composite adsorbent. In addition, linearization of the breakthrough curve by dynamic models was implemented to characterize the adsorption process by the composite adsorbent in ECPS column model. The linearization of breakthrough curve was done using mathematical models, Adam-Bohart, Yoon-Nelson and Thomas model. It was found that the optimal mixture ratio was at 75% cockleshells and 25% natural zeolite. Based on the experiments, the composite adsorbent showed high tendency to higher removal by 90% of targeted value. Based on the results, the composite adsorbent was fitted better with Yoon-Nelson and Thomas model rather than Adam-Bohart model. The generated models were able to characterize the adsorption process using composite adsorbent in the ECPS column system.